Clean Energy Technologies Hydrogen and Gasification Processes - Eyvaz, Murat; Yun, Yongseung; Albahnasawi, Ahmed (IntechOpen, 2022)
Increasing urbanization, population growth, and climate change require responsible consumption of all resources, primarily energy. Worldwide energy efficiency applications, renewable energy, and related technologies will be the driving force in the energy sector. It is envisaged that large amounts of carbon emissions can be prevented by changing the electricity production and consumption habits of societies and transforming them into renewable energy and related technologies in energy systems. This book presents valuable scientific studies on clean energy technologies and analyzes hydrogen production processes in detail.